Digital performance and posthhumanist anthropology - Λαλιώτη, Βασιλική (The Greek Review of Social Research, 2018)
Over the last two decades the incorporation of digital technologies in the performing arts has given rise to a wide discussion, within the field of performance studies, regarding performance ontology. Despite the variety of the views that have been formulated, this discussion to a great extent reproduces binarisms of mind/body, nature/culture, and human/technology, which have become limited frameworks through which to articulate the multiple ways in which participants are engaged in various digital performances. Departing from specific theoretical and methodological concerns that have been developed in posthumanist anthropology, in this paper I explore the ways in which questioning these binarisms may enrich the study of digital performance and lead to a deeper understanding of the relationship between humans and their environment within the frame of the emerging digital cultures.